Numerical and Experimental Study of Multiport Diffusers with Non-Uniform Port Orientation - Saeidihosseini, Seyedahmadreza (Université d'Ottawa / University of Ottawa, 2024)
Dense wastewater discharges into marine environments can severely impact water bodies. This study addresses the disposal of hypersaline brines from desalination plants through multiport diffusers into seas and oceans. Accurate prediction of the mixing of discharges with the receiving water bodies is crucial for the optimal design of outfall systems. Designers can enhance mixing and increase dilution by modifying outfall properties. However, the interaction of discharges from multiport diffusers poses a significant challenge, impairing the mixing process. The main aim of this study is to improve multiport diffuser designs by limiting the negative effects of jet interaction on mixing. This research applies a three-dimensional numerical model, the Launder, Reece, and Rodi (LRR) turbulence model, to evaluate the predictive capabilities of the Reynolds Stress Models (RSM) for multiple dense jets and to explore the mixing characteristics and merging process of multiple jets. To validate the model, its predictions are compared with available experimental data. The LRR model showed good agreement with the experimental measurements, and the model outperformed the standard and re-normalization group (RNG) 𝑘−𝜀 turbulence models, making it a promising tool for studying the mixing behavior of multiport diffusers. This study proposes multiport diffusers with non-uniform port orientation as a means for mitigating the negative effect of jet mering on the mixing process and increasing dilution. Using the validated numerical model and the laser-induced fluorescence (LIF) technique, the effect of non-uniform port orientation on the mixing process is explored. The numerical results indicated that the orientation of adjacent jets significantly affected the behavior of individual jets. An individual jet exhibited a longer trajectory and higher dilution when its neighboring jets were disposed of with a different angle, compared to that of uniform discharges. Laboratory experiments on uniform and non-uniform diffusers, with varying port angles in the range of highest reported dilution rates for single discharges (40o-70o), are reported, and the major flow properties and merging processes are compared. Investigations revealed that non-uniform diffusers achieved overall higher mean dilutions due to different mixing behavior in the interaction zones. Non-uniform port orientation provided more space between the jets to expand before interacting with their neighbors, resulting in higher dilutions. This study challenges the application of formulae obtained from single discharge experiments for multiport diffuser designs and emphasizes the importance of considering source characteristics specific to multiport diffusers, such as angle difference, for efficient desalination outfall. The new data and analysis provided in this study can benefit the design of desalination discharge systems with considerable potential cost savings, especially for tunneled outfalls, due to shorter diffusers with non-uniform port orientations and environmental risk reductions.
Keywords: Desalination; Brine disposal; Multiport diffuser; Numerical Simulations; Negatively buoyant jet; Discharge inclination